HUBUNGAN DURASI, JARAK &POSISI PENGGUNAAN SMARTPHONE TERHADAP KELELAHAN MATA PADA MAHASISWA ANGKATAN 2018 FAKULTAS KEDOKTERAN UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA - YONDHI ZALDI (JURNAL ILMIAH MAKSITEK, 2022)
Eye fatigue or also known as asthenopia is a general term used to describe a variety of non-specific symptoms related to the visual system. There are many risk factors that can cause eye fatigue, including reading without pause to rest the eyes, using smartphones in terms of duration of use, distance, and position of use, and exposure to dry air due to the use of fans or room cooling. Objective: To determine the relationship between duration, distance and position of smartphone use on eye fatigue in UMSU Medical Faculty students. Analytical with cross sectional study approach, sampling method using quota sampling technique. This research methods are the data of this study were obtained from primary data using a questionnaire instrument. Data analysis using Spearman rank test. This results are the number of students who became respondents. 44 students (77.2%), using smartphones with a distance of <3 cm (57.9%), using smartphones with a sitting position as many as 29 people (50.9% ). The conclusion there is a relationship between the duration of smartphone use and eye fatigue, and there is a relationship between the distance of smartphone use and eye fatigue, but there is no relationship between the position of smartphone use and eye fatigue in students of the Faculty of Medicine, University of Muhammadiyah North Sumatra.